EVALUASI KEPUASAN KLIEN TERHADAP HASIL PRODUK KONTRUKSI (Studi Kasus: PT Isa Putra Konstruksi) - Ristianto, Isnaini Prasetyo; Solikin, Mochamad; Harnaeni, Senja Rum; Sunarjono, Sri (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
1),A construction service company is a company engaged in the development sector in Indonesia. Construction contractor service business in the form of planning, design, cost calculation, bidding and construction implementation until completion. After all the work is completed, it will be handed over to the project owner or owner. The field of work for construction service companies is in the form of building construction, bridge construction, factory construction, industrial development and road construction. The aim of this study was to test and analyze the evaluation of the satisfaction and quality of service users at the construction company PT. Isa Putra Construction. The analytical method used in this research is a quantitative descriptive research type using Statistical Product and Service Solution (SPSS). The research was conducted at companies engaged in construction services, namely PT. Isa Putra Construction with a sample of 17 respondents. Based on the results of the calculations that have been done, the CSI value is 47%. This CSI value is obtained from the division between the total Weight Score (WS) value and the maximum scale used in this study, namely 5 and multiplying by 100%.Keywords: Satisfaction, Quality, Construction Services, Service User Satisfaction Construction